Effects of Artificially Reproduced Fluctuations in Sunlight Spectral Distribution on the Net Photosynthetic Rate of Cucumber Leaves - Matsuda, Ryo; Ito, Hiroki; Fujiwara, Kazuhiro (Frontiers in Plant Science, 2021)
The effects of photosynthetic photon flux density (PPFD) fluctuations in sunlight have already been investigated; however, the spectral photon flux density distribution (SPD) has hardly been considered. Here, sunlight SPD fluctuations recorded for 200 min in October in Tokyo, Japan were artificially reproduced using an LED-artificial sunlight source system. The net photosynthetic rate (Pn) of cucumber leaves under reproduced sunlight was measured and compared with the Pn estimated from a steady-state PPFD–Pn curve for the same leaves. The measured and estimated Pn agreed except when the PPFD was low, where the measured Pn was lower than the estimated Pn. The ratio of measured Pn to estimated Pn was 0.94–0.95 for PPFD ranges of 300–700 µmol m−2 s−1, while the value was 0.98–0.99 for 900–1,300 µmol m−2 s−1, and the overall ratio was 0.97. This 3% reduction in the measured Pn compared with the Pn estimated from a steady-state PPFD–Pn curve was significantly smaller than the approximately 20–30% reduction reported in previous experimental and simulation studies. This result suggests that the loss of carbon integral net photosynthetic gain under fluctuating sunlight can vary among days with different fluctuation patterns or may be nonsignificant when fluctuations in both PPFD and relative SPD of sunlight are taken into consideration.